Tight Junction Disruption Induced by Type 3 Secretion System Effectors Injected by Enteropathogenic and Enterohemorrhagic Escherichia coli - Ugalde-Silva, Paul; Gonzalez-Lugo, Octavio; Navarro-Garcia, Fernando (Frontiers in Cellular and Infection Microbiology, 2016)
The intestinal epithelium consists of a single cell layer, which is a critical selectively permeable barrier to both absorb nutrients and avoid the entry of potentially harmful entities, including microorganisms. Epithelial cells are held together by the apical junctional complexes, consisting of adherens junctions, and tight junctions (TJs), and by underlying desmosomes. TJs lay in the apical domain of epithelial cells and are mainly composed by transmembrane proteins such as occludin, claudins, JAMs, and tricellulin, that are associated with the cytoplasmic plaque formed by proteins from the MAGUK family, such as ZO-1/2/3, connecting TJ to the actin cytoskeleton, and cingulin and paracingulin connecting TJ to the microtubule network. Extracellular bacteria such as EPEC and EHEC living in the intestinal lumen inject effectors proteins directly from the bacterial cytoplasm to the host cell cytoplasm, where they play a relevant role in the manipulation of the eukaryotic cell functions by modifying or blocking cell signaling pathways. TJ integrity depends on various cell functions such as actin cytoskeleton, microtubule network for vesicular trafficking, membrane integrity, inflammation, and cell survival. EPEC and EHEC effectors target most of these functions. Effectors encoded inside or outside of locus of enterocyte effacement (LEE) disrupt the TJ strands. EPEC and EHEC exploit the TJ dynamics to open this structure, for causing diarrhea. EPEC and EHEC secrete effectors that mimic host proteins to manipulate the signaling pathways, including those related to TJ dynamics. In this review, we focus on the known mechanisms exploited by EPEC and EHEC effectors for causing TJ disruption.